2020
DOI: 10.1177/1367877920956655
|View full text |Cite
|
Sign up to set email alerts
|

Internetica: Poetry in the digital age

Abstract: This article proposes a new conceptual framework for understanding poetry in the age of the internet. By combining literary and technologic theories into one theory named ‘Internetica’, it typifies the structures and roles of internet poetry and poets. A grounded analysis of 200 poems revealed three types of web poems: poems about the internet, poems first published on the internet, and poems written through the internet. The analysis presents various distinctions among these three types of poems, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Humour is very present in internet culture. Shakargy (2021) found that all three studies of internet poetry used humour but tended to use it differently and for various purposes. The function of poetry in the digital era can also convey satire that is conveyed humorously but on the target of satire.…”
Section: Pantun Functionmentioning
confidence: 97%
“…Humour is very present in internet culture. Shakargy (2021) found that all three studies of internet poetry used humour but tended to use it differently and for various purposes. The function of poetry in the digital era can also convey satire that is conveyed humorously but on the target of satire.…”
Section: Pantun Functionmentioning
confidence: 97%
“…However, the internet has had important impacts on poetry and poetic communities. As Shakargy (2021) notes, the internet has resulted in “a significant increase in the number of texts that are considered poetry and the number of people who are considered poets,” (325). Spaces like Twitter (Raley, 2009) and Instagram (Kovalik & Curwook, 2019) offer readers places to find poets who are writing and living in ways they can identify with, about issues that are immediately relevant to their lives and interests.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…As a form of digital storytelling, online literature creation is technology-decided: literary works are created by computer-based tools and circulated on internet-based networks (Robin and McNeil, 2019). With the upgrading of the internet and its platforms, the creative expression of both professional and amateur literary writers has been expanded, leading to a significant increase in the number of both literary writers and works (Shakargy, 2021).…”
mentioning
confidence: 99%